RESPIRATORY SYNCYTIAL VIRUS INFECTION: CLINICAL AND LABORATORY FEATURES - E. V. Mikhaylova; T. K. Chudakova; M. S. Yarushkina; A. V. Romanovskaja; N. F. Кhvorostukhina (Детские инфекции (Москва), 2017)
Infants are dominated among patients with respiratory syncytial viral infection (RSVI). In patients with RSVI characteristic are lesions of the lower respiratory tract and development of bronchial obstruction. Laboratory indicators of intoxication (the level of CRP, Leukocyte index of intoxication (LII), hematologic indicator of intoxication (GPI), metabolic disorders and decreased oxygen saturation below 93% are indicators of the severity of the disease, which can predict the development of a more severe course of RSVI and its complications.